Living the dream - O'Donnell, Daniel 1961- (The O'Brien Press, 2017)
In Ireland, Daniel O'Donnell is more than just a singing star: he has reached the status of national treasure'. In this book he tells his story with his customary sense of humor and down-to-earth charm. He reflects on his wife Majella's battle with cancer; the death of his beloved mother, his part in the BBC's Strictly Come Dancing TV show; and his road trip adventures with Majella. And he delves into the relentless touring and recording that took him to the brink of burnout and forced him to reassess his priorities
Includes discography
Keywords: O'Donnell, Daniel -- 1961-; Geschichte 1961-; Folkmusiker; Sänger; Irland; O'Donnell, Daniel / 1961-; Country musicians / Ireland / Biography; Singers / Ireland / Biography; Country musicians; Singers; Ireland; Biography; Autobiografie; Diskografie